Silica : Physical Behavior, Geochemistry, and Materials Applications - Gibbs, Gerald V.; Heaney, Peter J.; Prewitt, Charles T. (Reviews in Mineralogy & Geochemistry ;, 2018)
Volume 29 of Reviews in Mineralogy provides an updated silica review which focuses on the most recent developments. This book describes the crystal structures and phase transitions of silica and its stuffed derivatives; bridges the relationship between the microstructural character of real silica minerals and the behavior of silica in the geological environment; covers Quantum mechanical considerations of the Si-O bond; shows how calculations based upon first-principles theory can explain and predict silica transitions at high temperatures and pressures; covers spectroscopic analyses of silica and how they reveal vibrational behaviors in response to variations in temperature, pressure, and composition and finally details the uses of silica for industrial purposes.